(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Eastern education is a system of spiritual and moral values characteristic of the peoples of the East, based on the principles of education passed down from generation to generation. Eastern education plays an important role in preserving family, society and national identity.